Endolysosomal degradation of Tau and its role in glucocorticoid-driven hippocampal malfunction - Vaz-Silva, João (2018)
Emerging studies implicate Tau as an essential mediator of neuronal atrophy and cognitive impairment in Alzheimer's disease (AD), yet the factors that precipitate Tau dysfunction in AD are poorly understood. Chronic environmental stress and elevated glucocorticoids (GC), the major stress hormones, are associated with increased risk of AD and have been shown to trigger intracellular Tau accumulation and downstream Tau-dependent neuronal dysfunction. However, the mechanisms through which stress and GC disrupt Tau clearance and degradation in neurons remain unclear. Here, we demonstrate that Tau undergoes degradation via endolysosomal sorting in a pathway requiring the small GTPase Rab35 and the endosomal sorting complex required for transport (ESCRT) machinery. Furthermore, we find that GC impair Tau degradation by decreasing Rab35 levels, and that AAV-mediated expression of Rab35 in the hippocampus rescues GC-induced Tau accumulation and related neurostructural deficits. These studies indicate that the Rab35/ESCRT pathway is essential for Tau clearance and part of the mechanism through which GC precipitate brain pathology.